Homeoffice im Zeichen der Pandemie: Neue Perspektiven für Wissenschaft und Praxis? - Mario Herrmann; Regina Frey Cordes (IUBH Internationale Hochschule, 2020)
– The covid-19-virus has been causing a global pandemic in 2020. As a result of the rapid spread of the virus, the German government has decided to restrict social contacts as much as possible. This also has an impact on companies that increasingly allow their employees to work from home. Both for science and practice there is the chance to gain new insights into remote-work. This article pursues three central questions: How widespread was remote-work in Germany before the Corona crisis? What special demands and resources are necessary for people to cope with the new situation (working at home)? And finally: What factors influence the performance, commitment and job-satisfaction of employees working at home?
Keywords: 650; Corona-crisis; remote-work; job-demands; job-ressources; commitment; job-satisfaction; performance